Olympians. 2, Athena, grey-eyed goddess - O'Connor, George (New York : First Second, 2010)
Retells, in graphic novel format, the Greek myth about Athena, the Greek goddess of wisdom and war.
"A Neal Porter Book"--T.p.
Cover title.
Genealogical table on inside front cover.
Includes bibliographical references (p. 76).
4.1
5-8
Keywords: Athena (Greek deity) -- Comic books, strips, etc. -- Juvenile fiction; Goddesses, Greek -- Comic books, strips, etc. -- Juvenile fiction; Mythology, Greek -- Comic books, strips, etc. -- Juvenile fiction; Athena (Greek deity) -- Fiction; Cartoons and comics; Fantasy; Goddesses, Greek -- Fiction; Mythology, Greek -- Fiction; Mythology -- Fiction; Athena (Greek deity) -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Fantasy graphic novels; Gods and goddesses -- Comic books, strips, etc. -- Fiction; Graphic novels; Greek mythology -- Comic books, strips, etc. -- Fiction; Mythology -- Comic books, strips, etc. -- Fiction; Fantasy comic books, strips, etc; Graphic novels